Leveraging the Power of the School District: A Mixed Methods Study of Accreditation Reports - Hart, Molly (Valdosta State University, 2011)
This research examined the nature of recommendations made to school districts by accreditation teams. The review of literature examined the standards used for district accreditation and found congruence with best practices for district improvement. School districts can contribute in specific ways to the improvement of education. Examining the recommendations of peer-review teams and correlating these by size, spending, and poverty provided information about district-wide improvement. Participants included 13 8 districts in the states served by the Southern Association of Colleges and Schools Commission on School Improvement (SACS CASI) who received District Accreditation from 2002-2007. Text analysis using the constant comparative method was executed to create numerical data, which was then analyzed using an ordinal regression technique. Districts had wide variances in recommendations made by peer-review teams. Results also showed that per pupil spending, percentage of students in poverty, and school district size were only marginally related to the elements of successful district practices. Further research is needed to clarify the relationships between demographic factors and factors of successful district practices.
Keywords: School Districts; SACS CASI; Accreditation; Student poverty